Epilogue: Moral Panics and Body Cameras - Howard M. Wasserman (Washington University Law Review, 2015)
This brief follow-up to Moral Panics and Body Cameras comments on the weeks after that essay was published and what those events show about the efficacy of body cameras and video evidence as a response to police-public conflicts.
Keywords: Civil Rights Law; Police body cameras; Body cameras; Ferguson Missouri; Ferguson; Michael Brown